2020
DOI: 10.1001/jamainternmed.2020.0064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Single-Component and Multicomponent Interventions for Reducing Radiation Doses in Patients Undergoing Computed Tomography

Abstract: IMPORTANCE Computed tomography (CT) radiation doses vary across institutions and are often higher than needed.OBJECTIVE To assess the effectiveness of 2 interventions to reduce radiation doses in patients undergoing CT. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial included 864 080 adults older than 18 years who underwent CT of the abdomen, chest, combined abdomen and chest, or head at 100 facilities in 6 countries from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The University of California San Francisco (UCSF) International CT Dose Registry includes 6.65 million CT exams assembled from across 160 hospital and imaging facilities [ 6 , 7 ]. The registry was created with funding from the University of California Office of the President, the Centers for Disease Control and Prevention, the National Institutes of Health and the Patient Centered Outcomes Research Institute, and includes data from health care institutions that used Radimetrics Radiation Dose Management Solution (Bayer HealthCare, Whippany, NJ) and expressed interest in collaborating with UCSF on radiation-related research.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The University of California San Francisco (UCSF) International CT Dose Registry includes 6.65 million CT exams assembled from across 160 hospital and imaging facilities [ 6 , 7 ]. The registry was created with funding from the University of California Office of the President, the Centers for Disease Control and Prevention, the National Institutes of Health and the Patient Centered Outcomes Research Institute, and includes data from health care institutions that used Radimetrics Radiation Dose Management Solution (Bayer HealthCare, Whippany, NJ) and expressed interest in collaborating with UCSF on radiation-related research.…”
Section: Methodsmentioning
confidence: 99%
“…ratio) between phantom sizes (16 cm vs. 32 cm) to measure the magnitude of difference due to reference phantom selection when there were at least 5 CT examinations performed by age and body region using each phantom. The Radimetrics dose tracking platform was employed to extract all patient, scanner and exam variables (see [ 6 , 7 ] for details), and SAS (version 9.3; SAS Institute, Cary, NC) and R (version 3.6.3; R Foundation for Statistical Computing, Vienna, Austria) were used for all analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature cites numerous publications that are related to the optimization process and patient dose reductions [41,. For example, Smith-Bindman R et al applied customized optimization steps in 100 facilities for 864 080 adult patients and 1,156,657 CT scans, and reported that detailed feedback on CT radiation dose combined with actionable suggestions and quality improvement education significantly reduced doses, whereas the effects of audit feedback alone were modest [68]. The same authors in another study that included hospitals from around the world (over 2 million CT examinations of adult patients from 151 institutions in Switzerland, Netherlands, Germany, United Kingdom, United States, Israel, and Japan), concluded that the dose variation across countries was primarily attributable to institutional decisions regarding the technical parameters of CT protocols rather than patient, institution or machine characteristics [69].…”
Section: Step 5: Evaluation Of Optimization Process: Effect In Patient Dose and Image Qualitymentioning
confidence: 99%